Downregulation of Soluble Guanylate Cyclase and Protein Kinase G With Upregulated ROCK2 in the Pulmonary Artery Leads to Thromboxane A2 Sensitization in Monocrotaline-Induced Pulmonary Hypertensive Rats - Cho, Suhan; Namgoong, Hyun; Kim, Hae Jin; Vorn, Rany; Yoo, Hae Young; Kim, Sung Joon (Frontiers in Physiology, 2021)
Thromboxane A2 (TXA2) promote various physiological responses including pulmonary artery (PA) contraction, and the pathophysiological implication has been suggested in cardiovascular diseases including pulmonary hypertension. Here we investigate the role of TXA2 receptor (TP)-mediated signaling in the pathophysiology of pulmonary arterial hypertension (PAH). The sensitivity of PA to the contractile agonist could be set by relaxing signals such as nitric oxide (NO), soluble guanylate cyclase (sGC) and cGMP-dependent kinase (PKG) pathway. The changes of TP agonist (U46619)-induced PA contraction and its modulation by NO/cGMP signaling were analyzed in monocrotaline-induced PAH rat model (PAH-MCT). In the myograph study, the PA from PAH-MCT showed higher responsiveness to U46619, i.e. decreased EC50. Immunoblot analysis revealed lower expression of eNOS, sGC and PKG while higher expression of RhoA-dependent kinase 2 (ROCK2) in the PA from PAH-MCT than control. In the PAH-MCT, the higher sensitivity to U46619 was reversed by 8-Br-cGMP, a membrane permeable cGMP analogue, while not by NO donor, sodium nitroprusside (SNP 30 µM). Vice versa, in the control PA, inhibition of sGC by its inhibitor (ODQ, 10 µM) lowered the threshold of U46619-induced contraction. In the presence of ODQ, SNP treatment had no effect whereas the addition of 8-Br-cGMP lowered the sensitivity to U46619. The inhibition of ROCK by Y-27632 commonly attenuated the sensitivity to U46619 in both control and PAH-MCT. The study suggests that the attenuation of NO/cGMP signaling and the upregulation of ROCK2 increase the sensitivity to TXA2 in the PAH animal, which might have pathophysiological implication in the PAH patients.